The Development of Data Warehouse from Payment Point Services of IT Business Solution Provider - Kornelius Irfandhi (ComTech: Computer, Mathematics and Engineering Applications, 2017)
The goals of the research is to develop a data warehouse loaded from operational database of payment point service in IT business solution provider. The development scope is data analysis using Online Analytical Processing (OLAP) tools for identifying the trends of transaction and agent registration, and create reports and dashboards. The data warehouse was developed with Kimball method as known as the nine-step design methodology. The data and requirement were collected by observation and interview with Chief Technology Officer (CTO). The data warehouse was analyzed by OLAP tool provided by Pentaho Business Analytics software with additional plugin Pivot4J. The obtained results are the trends of transactionand agent registration between 2014 and 2015. It can be concluded that developed data warehouse can be used as ananalysis tool to know the trends information.